Australian general practice registrars and their experience with postpartum consultations: A cross‐sectional analysis of prevalence and associations. (7th July 2019) - Hill, Sophia; Tapley, Amanda; van Driel, Mieke L.; Holliday, Elizabeth G.; Ball, Jean; Davey, Andrew; Patsan, Irena; Spike, Neil; Fitzgerald, Kristen; Morgan, Simon; Magin, Parker
Abstract : Background: In Australia, general practitioners (GPs) are recognised as an essential source of postpartum care. However, there remains a paucity of research pertaining to this, and in particular, to that of GP trainees (in Australia, termed 'registrars'). Previous post‐graduate experience in obstetrics and gynaecology (O&G) is not a prerequisite for GP training, and thus, it is imperative that vocational training provides adequate exposure to postpartum consultations. Aim: To investigate the prevalence and associations of Australian GP registrars' (trainees') experience in postpartum care. Materials and Methods: A cross‐sectional study employing data from the Registrar Clinical Encounters in Training (ReCEnT) project. ReCEnT is an ongoing cohort study where GP registrars record 60 consecutive consultations mid‐way through each training term. The outcome variable was postpartum problem/diagnosis (compared to all other problems/diagnoses). The independent variables included registrar, practice, patient, consultation, clinical and educational factors. Analyses employed univariate and multivariable regression. Results: Analysis included 2234 registrars (response rate 96.1%), 289 594 consultations, and 453 786 problems/diagnoses. Postpartum care (897) comprised 0.2% (95% CI: 0.19–0.21) of all problems/diagnoses in 0.3% (95% CI: 0.27–0.31) of all consultations. Significant multivariable associations included registrar's gender (female) and obtainment of post‐graduate O&G qualifications. Postpartum consultations were longer and resulted in more learning goals being generated. Discussion: An overall low prevalence was established. Both male registrars, and those without pre‐existing O&G qualifications, may have particularly limited experience. These findings should inform educational policy and practice regarding postpartum care experience in general practice training.